Effects of running exercise combined with blood flow restriction on physical response and muscular fitness in athletes - Yun Tsung, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Muscular fitness (strength and endurance) not only improves sports performance, but also reduces the risk of injury. Recent studies show that low-intensity resistance training (LIRT) combined with blood flow restriction (BFRE) leads to an increase in the metabolic stress. It is well known that LIRT+BFRE improves the muscle adaptations such as strength and endurance gains. However, running exercise combined with BFRE on acute physiological responses and muscle performance is still unknown. Thus, the purpose of the present study was to investigate the effect of running exercise+BFRE on blood lactate (BLa), muscle tissue O2 saturation (MTOS), strength and endurance performance in athletes. Methods: 12 male athletes were recruited to participate in this study. All participants received two treatments: (1) Running exercise with BFRE (RB). (2) Running exercise without BFRE (R). Following a 5 min rest after the treatment, strength and endurance were determined using a Biodex System. Ratings of perceived exertion (RPE) were recorded (pre-ex, post-ex, 5 min postex, post-test) using the Borg RPE Scale. BLa (pre-ex, 3 min post-ex, 3 min post-test) and MTOS (from 5 min pre-ex to 5 min post-ex) were determined using lactate meter and near-infrared spectroscopy. A one-way ANOVA with repeated measures was performed to examine the muscular fitness differences between the treatments. A two-way ANOVA with repeated measures was used to evaluate the treatment effects for the others variables. Results: Following the treatment, isokinetic knee flexion strength (60º/s) was greater in the RB treatment than in the R treatment. There were no differences between the two treatments for isokinetic knee extension strength (60º/s, 180º/s) and knee flexion strength (180º/s). With respect to isokinetic endurance, there was no difference between RB exercise and R exercise. RPE was higher in the RB treatment than in the R treatment at post-ex. BLa was higher in the RB treatment than in the R treatment at 3 min post-ex. MTOS was lower in the RB treatment than in the R treatment during-ex and 5 min post-ex. Discussion: In the present study showed that RB treatment has no effect on isokinetic knee extension strength (60º/s, 180º/s), knee flexion strength (180º/s) and endurance performance, because a single bout of RB treatment did not cause any change in the muscle adaptations. Previous studies suggest that LIRT+BFRE result in muscular ischemic conditions, thus increase in motor unit recruitment, such as type II fibers (Wernbom et al., 2009; Yasuda et al., 2009). Increasing in motor unit recruitment was the possible explanation for improvement on isokinetic (60º/s) knee flexion strength after the RB treatment. The RB treatment increased the RPE and muscular metabolic stress were similar to previous studies. Given the muscular fitness improvements associated with resistance training, a RB treatment may be an effective training program for promoting muscle adaptations in practical applications.